Strategi Alih Tutur pada Gelar Wicara Mata Najwa Episode “Beres-Beres Kursi Menteri Kesehatan”: Kajian Analisis Percakapan - Putra, Pebri Prandika (Jurnal Bahasa dan Sastra, 2024)
This research investigates the dynamics of turn-taking within a talk show context, specifically focusing on the "Beres-Beres Kursi Menkes" episode of Indonesia's Mata Najwa. Utilizing a qualitative content analysis methodology involving recording and note-taking, the study examines turn-taking behaviors based on Stenström's (1994) theoretical framework. The analysis reveals three primary strategies: Taking the Floor, Holding the Floor, and Yielding the Floor. The conversation unfolds through bidirectional interactions, characterized by initial greetings, instances of overlapping speech, intermittent interruptions, and a concluding prompt. The study underscores the significance of mastering the Taking the Floor strategy, which involves seizing speaking opportunities, initiating or responding to turns, and rectifying errors. Proficiency in this aspect facilitates meaningful dialogues and ensures a coherent exchange of ideas within the context of talk shows.